2005
DOI: 10.1007/s11205-004-6397-8
|View full text |Cite
|
Sign up to set email alerts
|

The Wealth of Nations and the Happiness of Nations: Why “Accounting” Matters

Abstract: happiness, income, life satisfaction, national well-being, subjective well-being,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 103 publications
1
37
0
5
Order By: Relevance
“…Diener and Biswas-Diener also suggested that income may have either a direct influence or an indirect influence, through financial satisfaction, on subjective well-being. Arthaud-Day and Near (2005) reached similar conclusions in their more focused review of the relationship between income and happiness within nations and across nations. A newer study using data collected from five countries indicated effects of wealth and non-durable consumptions on life satisfaction (Headey et al 2008).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 58%
“…Diener and Biswas-Diener also suggested that income may have either a direct influence or an indirect influence, through financial satisfaction, on subjective well-being. Arthaud-Day and Near (2005) reached similar conclusions in their more focused review of the relationship between income and happiness within nations and across nations. A newer study using data collected from five countries indicated effects of wealth and non-durable consumptions on life satisfaction (Headey et al 2008).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 58%
“…Various researchers have cited Maslow's theory of hierarchy of needs to explain the strong association between economic status and subjective well-being as well as the diminishing marginal effect of economic status on subjective well-being as income and wealth increase [55][56][57][58][59][60]. Several studies have demonstrated that households expressing dissatisfaction with the availability of food, housing, hygiene, health services, or clothing report significantly lower subjective well-being, on average, than do households whose basic needs are reported to be satisfied [57,59,61,62].…”
Section: Discussionmentioning
confidence: 99%
“…İlgili alan yazında gelir ve mutluluk arasındaki ilişkiyi açıklamada üç farklı teoriden sıklıkla faydalanılmaktadır. Bunlar; beklenti teorisi (expectation theory), adaptasyon teorisi (adaptation theory) ve son olarak sosyal kıyaslama teorisidir (social comparison theory) (Diener vd., 1993;Arthaud-Day & Near, 2005;Dumludag, 2013;Caner, 2014).…”
Section: Introductionunclassified